Adaptive processing of image using DWT and FFT OFDM in AWGN and Rayleigh channel - Mannan, Abdul; Habib, Aamir (2017 International Conference on Communication, Computing and Digital Systems (C-CODE), 2017)
Wireless communication has a very important role in the day to day life for everyone. The wireless technology is growing rapidly and there is a growing demand of high performance, capacity and larger bit rate wireless communication systems which cope wireless communication services such as high speed data, video and voice signals. Multicarrier modulation scheme like OFDM provides an efficient solution to overcome this problem. In this paper a gray scale image processing is done using a LMS algorithm with wavelet based OFDM system using the QPSK modulation scheme in AWGN and Rayleigh channel in SISO environment and results are compared with the conventional adaptive FFT based OFDM system. We reconstruct our transmitted signal at receiver; in both systems by minimizing the error by adaptive filter but the computational complexity of FFT based system is more as compared to DWT based system. Results are compared in term of SNR vs BER which shows that adaptive DWT based OFDM system perform better as compared to the conventional adaptive FFT OFDM system.